Factors associated with necrotizing soft tissue infections in pediatric population at a high-complexity reference centre - Andres Ramirez; Ivan Molina; Juan Valero; Daniela Moreno; Fernando Fierro; Vicky Cardenas (Elsevier, 2023)
Aim: To characterize the pediatric population that presented necrotizing soft tissue infection at the Fundación Hospital Pediátrico la Misericordia (HOMI) Methods: This was a retrospective study of pediatric patients with diagnosis of necrotizing soft tissue infections treated by the pediatric surgery service at HOMI, a referral hospital for oncological pediatric patients over a 5-year period (2017 to 2021). A descriptive analysis was performed. Results: The study included 52 patients, 65.4% were female, the average age was 8.1 years (sd: 5.53). The infection was most frequently located in the perineum (59.6%). Early symptoms were present in 88.5% (pain being the most frequent) and late symptoms in 73.1%. All but one patient had identifiable risk factors for infection, immunocompromised was the most frequent (73.1%), followed by oncological diagnosis (51.9%) and surgical procedures (abdominoperineal, colostomy and bone marrow biopsy, with 13.3% each one) All patients underwent surgical debridement (mean 3 procedures per patient, SD: 2.0) and 32.7% underwent colostomy. The most isolated microorganism in the tissues in monomicrobial and polymicrobial infections was Escherichia coli (11.5% in each group). 57.7% required management in the Intensive Care Unit. The average mortality was 23.1%, being higher in patients with acute lymphoblastic leukemia and neutropenia (35.0%). Conclusion: In the present study, the highest frequency of soft tissue infections was in the immunosuppressed and oncological population. The characteristics of our study and mortality were different from those described in the literature due to the predominance of this population.